La retraduction : le sort de la conception bermanienne en Finlande - Kristiina Taivalkoski-Shilov (Romanica Wratislaviensia)
The purpose of this article is to examine the impact of Antoine Berman’s theory of retranslation in Finland. The role of Yves Gambier, Andrew Chesterman and Kaisa Koskinen & Outi Paloposki as mediators of Berman’s theory is explored. The close reading of their articles on retranslation from the 1990s and early 2000s shows that they all have contributed to linking Berman to the “retranslation hypothesis” that is nowadays considered a simplification of his complex theory (K. Peeters, P. Van Poucke, « Retranslation, thirty-odd years after Berman », Parallèles 35(1), 2023, pp. 3–27). Furthermore, contrary to what is usually claimed the notorious hypothesis does not originate from Chesterman. Secondly, the study investigates Berman’s influence in Finland by analyzing doctoral dissertations that have examined retranslations. It is concluded that although few Finnish dissertations properly use the Bermanian framework, his influence in Finland has been significant through Koskinen & Paloposki’s studies that have adopted the complex Bermanian framework from the 2010s onwards. Finally, it suggests that Berman’s ideas on the incompleteness of translation and the need for retranslation can also be applied, with modifications, to the study of the transmission of theories.